2006
DOI: 10.1084/jem.20051438
|View full text |Cite
|
Sign up to set email alerts
|

B cell–deficient NOD.H-2h4 mice have CD4+CD25+ T regulatory cells that inhibit the development of spontaneous autoimmune thyroiditis

Abstract: Wild-type (WT) NOD.H-2h4 mice develop spontaneous autoimmune thyroiditis (SAT) when given 0.05% NaI in their drinking water, whereas B cell–deficient NOD.H-2h4 mice are SAT resistant. To test the hypothesis that resistance of B cell–deficient mice to SAT was due to the activity of regulatory CD4+CD25+ T (T reg) cells activated if autoantigen was initially presented on non–B cells, CD25+ T reg cells were transiently depleted in vivo using anti-CD25. B cell–deficient NOD.H-2h4 mice given three weekly injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(131 citation statements)
references
References 55 publications
12
118
1
Order By: Relevance
“…Recently, we (5) and others (25) have discovered that the CTLA4 SNPs are strongly associated with T1D but in only those T1D cases with AITD autoantibodies or diagnosed AITD. Our interpretation of the results from these human studies on CTLA4 is based on our current and previous observations in the NOD mouse model: the strength of the effect of allelic variation of Ctla4 is very dependent on different combinations of other susceptibility loci, including complete masking of the effect (that is no association with disease), and different combinations of Idd loci give rise to quite different autoimmune phenotypes within the general NOD genetic background, including AITD and an autoimmune liver disease (26,27). It is likely that the genetic basis of human T1D and related diseases that occur more frequently together in T1D cases and families than expected, such as AITD and rheumatoid arthritis, is similar: different sets of alleles from multiple loci give rise to different but related diseases.…”
Section: Human Gene Discovery and Disease Subclassificationmentioning
confidence: 99%
“…Recently, we (5) and others (25) have discovered that the CTLA4 SNPs are strongly associated with T1D but in only those T1D cases with AITD autoantibodies or diagnosed AITD. Our interpretation of the results from these human studies on CTLA4 is based on our current and previous observations in the NOD mouse model: the strength of the effect of allelic variation of Ctla4 is very dependent on different combinations of other susceptibility loci, including complete masking of the effect (that is no association with disease), and different combinations of Idd loci give rise to quite different autoimmune phenotypes within the general NOD genetic background, including AITD and an autoimmune liver disease (26,27). It is likely that the genetic basis of human T1D and related diseases that occur more frequently together in T1D cases and families than expected, such as AITD and rheumatoid arthritis, is similar: different sets of alleles from multiple loci give rise to different but related diseases.…”
Section: Human Gene Discovery and Disease Subclassificationmentioning
confidence: 99%
“…Despite the benefits of this immunotherapy, the cellular and molecular basis for the protective effect mediated by B cell depletion is unknown (4). Understanding the mechanisms underlying the therapeutic benefit of B cell depletion is complicated by the fact that B cells not only produce autoantibodies (5) but also release inflammatory or immunomodulatory cytokines (6), regulate lymphoid tissue neogenesis and structure, provide costimulatory signals, alter dendritic cell (DC) function and homeostasis (7), can function as antigen-presenting cells, promote naïve CD4 ϩ T cell differentiation into Th1 or Th2 subsets, and may influence regulatory T cell numbers and function (8).…”
mentioning
confidence: 99%
“…B-cell-deficient NOD.H-2 h4 mice are AIT resistant and do not develop AIT even when reconstituted with B cells or given passive anti-murine Tg autoantibodies. However, when CD25 + Treg cells are transiently depleted in vivo using anti-CD25, these mice develop AIT with thyroid lesions similar to those observed in wildtype NOD.H-2 h4 after 8 weeks NaI provision [19]. Nakahara et al reported that in situ adenovirus transfectioninfection of TNF-related apoptosis-inducing ligand to the thyroid glands 1 day or 4 weeks before providing NOD.H-2 h4 mice with iodized water significantly suppressed thyroiditis by increasing the ratios of Tregs to CD4+ T cells in the lesion [20].…”
Section: Discussionmentioning
confidence: 63%